Periodontal Manifestations in a Patient with Haim-Munk Syndrome - Erciyas, Kamile; Inaloz, Serhat; Erciyas, A. Fuat (European Journal of Dentistry, 2010)
Haim-Munk syndrome is an extremely rare autosomal recessive disorder characterized clinically by palmoplantar hyperkeratosis, aggressive periodontitis with severe alveolar bone destruction, onychogryphosis, pes planus, arachnodactyly, and acro-osteolysis. Consanguinity seems a notable prerequisite. The aim of this study was therefore to report one case of this syndrome and to focus on the periodontal manifestations, in order to attract the attention of dental clinicians to this rare anomaly. (Eur J Dent 2010;4:338-340)
Keywords: Periodontitis; Haim-Munk syndrome; Palmoplantar keratoderma